Introduction: studying political violence while indicted – against objectivity and detachment. Issue 3 (3rd July 2019) - Loadenthal, Michael
ABSTRACT: Knowledge construction should seek to embrace empiricism – the deriving of knowledge from data and experience – while not confusing this with a false notion of objectivity. As a truly objective approach is not only difficult but likely impossible to establish, it obscures the burden placed upon social scientists by sociologist C. Wright Mills who advocated for the study of society in order to change it. This action-centric, emancipatory-focused approach is a hallmark of the critical turn in the investigation of political violence. Regardless of how neutral scholars and teachers may try to appear, what does it mean when our audience – our readers, colleagues and students – glimpse behind the curtain and begin to understand knowledge producers as three-dimensional political actors with subjectivities, positionalities and passions? Upon embarking on a multi-semester research and writing process with undergraduate students, what did it mean to begin such a relationship only hours after being released from federal custody, and how did my position vis-à-vis powerful juridical discourses shape our collaborative scholarship and the process of shared knowledge construction?